Food Security of Banjar People In Facing Climate Change In Sungai Batang Village, Banjar District, South Kalimantan - Setia Budhi; Sri Hidayah; Ismar Hamid; Siti Aulia; Muhammad Agrianto Suwandi (Wadah Inovasi Indonesia, 2021)
In the last five years, the world's attention has shifted to food security in relation to climate change adaptation and mitigation, particularly in 2008, when food prices skyrocketed, causing famine in Cape Africa and even the Sahel, which is still feeling the effects of this famine in 2012. In the same year, the OHCHR report (the Office of the United Nations High Commissioner for Human Rights) notes the need to safeguard food security and nutrition in the context of Human Rights. A major shift occurred in Indonesian agriculture due to the 1999 eruption of Mount Elanor. A focus on climate influences has been a prominent component of the Indonesian government's policy regarding agriculture for some time. Plant-resistant crops or programs for mitigating climate change take the form of either of these options. Culminating a significant development in policies to secure food security, such as protection of agricultural land, various policies were created to evaluate land use and regulations of the Minister of Agriculture pertaining to guidelines for land use. The study, which was done for a period of six months, has a goal of learning more about the Banjar people's local knowledge on climate change. By collecting data from locals, such as farmers, community leaders, and village heads, who have detailed knowledge about Banjar customs and traditions, and from Banjar people who are selected for the research in Banjar Regency, South Kalimantan, qualitative methods and collection of local knowledge and local wisdom strategies were employed.